Effect of Sm2O3 substitution on mechanical and biological properties of 45S5 bioactive glass - Ershad M.; Vyas V.K.; Prasad S.; Ali A.; Pyare R. (My University, 2025)
Synthesis and characterization of bioactive glasses having a general composition of (45 − X) SiO2, 24.5 Na2O, 24.5 CaO, and 6 P2O5 (where X = 0–4.0 wt% of Sm2O3) were studied. These glasses were melted in the alumina crucible at a temperature of 1400 ± 5 °C with air as a furnace atmosphere. Differential thermal analysis (DTA) was carried out at a heating rate of 10 °C per min under argon gas atmosphere using alumina as reference material in the temperature range of 100 to 1000 °C. From the DTA curve, nucleation and crystal growth temperature was determined and found to decrease with increasing content of Sm2O3. The glass samples were immersed in simulated body fluid (SBF) for different time periods, and bioactivities were measured using FTIR and pH. It was observed that the bioactivity of glass increased with increasing concentration of Sm2O3. Microstructures were evaluated by a scanning electron microscope (SEM). Density and other mechanical properties such as flexural, compressive, and microhardness were measured and were found to increase with increasing concentration of Sm2O3. © 2018, Australian Ceramic Society.